ANALYSIS OF CSR IMPLEMENTATION AND CURRENT RATIO ON STOCK PRICES OF CONVENTIONAL BANKING LISTED ON IDX 2016-2020 - Pradani, Devi Dias; Widiasmara, Anny (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
There are several ways that can be used by investors in determining whether or not a company is good. Such as looking at the way in which CSR has been implemented by the company or looking at the company's annual financial statements. According to Untung (2009:1): "Corporate Social Responsibility" is the commitment of the company or the business world to contribute to sustainable economic development by paying attention to corporate social responsibility and focusing on sustainability between attention to economic, social and environmental aspects. The purpose of this research is to provide scientific evidence that Current Ratio and CSR can affect stock prices. This type of research is quantitative research. With descriptive statistical test research methodology, multiple linear regression analysis and t test. With a sample of 20 conventional banking companies at www.idx.co.id. The test results show that the current ratio and CSR variables have a significant effect on stock prices.